Caseflow Management and Delay Reduction in Urban Trial Courts of the United States, 1979, 1983-1985 - Mahoney, Barry ([Verlag nicht ermittelbar], 1995)
The purpose of this study was to examine caseflow management in order to reduce delays in urban trial courts. The data contain information from court records that reached disposition in a cross-section of urban general-jurisdiction trial courts during 1979, 1983, 1984, and 1985. The 1979 data files contain the baseline data for this survey. Data were gathered on civil and criminal case processing times across a broad range of courts, and changes in case processing times over a period of years were analyzed for 18 different jurisdictions: Newark, Pittsburgh, New Orleans, Miami, Wayne County, Minneapolis, the Bronx, Phoenix, Portland, San Diego, Dayton, Boston, Cleveland, Providence, Wichita, Detroit, Oakland, and Jersey City. The data are supplemented by information supplied by trial court administrators and presiding judges in the courts participating in the study. Data include information on the nature of the case, the dates of first and last trials, and the total number of trials and their manner of disposition.